Histopathologic features of alcoholic cardiomyopathy compared with idiopathic dilated cardiomyopathy - Li, Xuebiao (Medicine (Baltimore), 2018)
BACKGROUND: The histologic difference between alcoholic cardiomyopathy (ACM) and idiopathic dilated cardiomyopathy (IDCM) is unclear. The present study aimed to identify the quantitative pathologic features of ACM compared with IDCM. METHODS: Specimens from 6 regions (anterior left ventricle [LV], lateral LV, inferior LV, interventricular septum [IVS], anterior right ventricle [RV], and inferior RV) were sampled from each explanted heart. Specimens from 4 healthy donor hearts were obtained as normal control. Tissues were sectioned and Masson trichrome stained. Histomorphometry was performed to evaluate the amount of myocyte, fibrosis, fatty tissue, and interstitium by Image-Pro Plus 6.0 (Media Cybernetics). RESULTS: A total of 408 specimens were obtained from 34 ACMs and 34 IDCMs; 8 specimens were obtained from 4 healthy donor hearts. Compared to healthy donor hearts, we observed an increase in fibrosis which replaces myocytes in myocardium of end-stage cardiomyopathy. The overall myocyte ratio in myocardium was 69.5 ± 8.7% in ACM vs 71.9 ± 7.4% in IDCM (P < .05). The percentage of interstitium was 10.8 ± 4.8% in ACM vs 9.2 ± 6.2% in IDCM (P < .05). A significant difference of fibrosis, fatty tissue was not discovered. Moreover, the myocyte area was 65.37 ± 11.8% in ACM LV vs 70.03 ± 9.0% in IDCM LV (P < .001). CONCLUSION: We described histologic characteristics in ACM and IDCM. There might be a quantitative difference of myocyte, interstitium in myocardium between ACM and IDCM, especially in LV. No difference was found in the percentage of fibrosis between the 2 groups.